Ethnic differences in the prevalence of polymorphisms in CYP7A1, CYP7B1 AND CYP27A1 enzymes involved in cholesterol metabolism - Vera Dias; V Ribeiro (Wolters Kluwer Medknow Publications, 2011)
It is well known that drug disposition and response are greatly determined by the activities of drug metabolizing enzymes, which are polymorphic. Some of these polymorphisms are clinically relevant and presented an ethnic-dependent pattern of distribution. The characterization of the genetic distribution of different populations allows the selection of therapeutic options in accordance with the genetic background, with the objective to avoid adverse reactions and inefficacy of the treatment. In this work, we studied selected genetic polymorphisms in drug metabolizing enzymes in three different ethnic groups - Portugal, Mozambique and Colombia. Polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) genotyping methods were developed for drug metabolizing enzymes, namely, cholesterol 7α-hydroxylase (CYP7A1) (−203A>C, −346C>T, −496C>T, N233S, G347S), sterol 27-hydroxylase (CYP27A1) (R164W, A169V, D273N, V400A) and oxysterol 7α-hydroxylase (CYP7B1) (−116C>G, R324H, 1774C>T) to characterize the allelic distribution of these polymorphisms among three different ethnic/geographic origins. A total of 12 CYP7A1, CYP27A1 and CYP7B1 genetic variants were genotyped in a sample of 92 Portuguese, 151 Mozambican and 91 Colombian subjects. The variants N233S in CYP7A1 and 1774C>T in CYP7B1 were not detected in any population studied. The promoter polymorphisms in CYP7A1 (−203A>C, −346C>T, −496C>T) had high frequency in the three ethnic groups. G347S (CYP7A1), R164W, A169V and V400A (CYP27A1) were present in a low frequency but with a similar distribution in the three ethnic groups. Significant differences were observed for D273N (CYP27A1), −346C>T (CYP7A1), −116C>G and R324H (CYP7B1)Our results demonstrate a high variability of drug metabolizing enzymes between the different populations analyzed, indicating that at least some of these polymorphisms are ethnic specific.